Community-Based Breeding Programs Continue to be Integrated into Higher Education Programs in Ethiopia - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Community-Based Breeding Program (CBBP) is an alternative genetic improvement program ICARDA and its partners run. Universities have been engaged in running CBBP since 2021 and have supported more than 63 CBBPS by investing more than 1.2 million USD till 2024. In 2024, three Universities supported 6 CBBP villages by investing more than 66,923,928 Birr (63018 USD) and benefiting more than 4000 family members. CBBP is also used to generate longitudinal data and use the data for PG thesis and dissertations in which more than five postgraduate candidates are beneficiaries of CBBP activities. Two Universities have amended CBBP in three courses that will benefit more than 40 and 10 students per year in UG and PG programs, respectively. The total number of beneficiaries, both from the community and students’ perspectives, is 4050. There is a need to fine-tune the CBBP program per the standard and engage more universities to expand the CBBP activity plan a breed-level improvement through CBBP implement the scaling framework and encourage the initiation of women-led CBBPs by each university and contribute to women empowerment and tapping the inherent linkage women and small ruminants.